Kontribusi Pola Asuh Orangtua Dan Konformitas Teman Sebaya Terhadap Perilaku Agresif Siswa Kelas VIII SMP Negeri 2 Kota Solok - Rahma Fitri Annisa; Mega Iswari; Dahranis Dahranis (Keguruan, 2022)
Parental parenting has an important role also for the development of moral behavior in children. The Indonesian Child Protection Committee (KPAI) assessed that the way of interacting with educated children this year was quite high due to aggressive behavior. In a society, aggressive attitudes are behaviors or attitudes that are widely disliked and tend to be avoided. This is because in social interaction, aggressiveness leads to danger and behavior. At the beginning of adolescent development, the family is the most important environment. The style or way of parenting each parent in educating their children is also different. There are parents who want to discuss or be open in any case to their children and there are also parents who do not want to discuss or be closed in any case to their children. At this time parents, families and the environment play a big role in the development of children, so that they can successfully go through the development process.